Immune Cells Expansion from Peripheral Blood of Some Vietnamese Cancer Patients - Thao, Chu Thi; Anh, Bui Viet; Phong, Nguyen Van; Kien, Nguyen Trung; Tu, Nguyen Dac; Hiep, Doan Trung; Liem, Nguyen Thanh; Nhung, Hoang Thi My (VNU Journal of Science: Natural Sciences and Technology; Vol 37 No 3, 2021)
Immunotherapy recently attracted high attention of scientists in cancer treatment. However, this therapy is poorly studied and applied in Vietnam. In this report, we present the results of immune cell ex vivo expansion for cancer treatment. After 20-21 days of culture, the average number of CD3 + CD8 + cytotoxic T lymphocytes (CTLs) increased by 633.6-fold, equivalent to 3,277.5 × 10 6 cells, and with the cell viability of  96.3%. Among them, the increasing folds of lung, liver and gastric cancer patients were 232.4, 812.4 and 655.6, respectively. Meanwhile, the average number of CD3 - CD56 + natural killer (NK) cells increased by 940.3-fold, equivalent to 2,659.3 × 10 6 cells, with the cell viability of 95%. Gastric cancer patients had the highest-fold NK cell expansion (1,644.9-fold) compared to that in lung cancer patients (695.0-fold), and liver cancer patients (358.3-fold). These results revealed that our method of immune cell expansion met the requirements in the immune cell number for clinical applications in cancer treatment in Vietnam.